Analysis of Student Needs in Interactive Multimedia-Based Mathematics Learning to Improve Problem-Solving Skills Using the Design Thinking Method - Fina Ismatul Uyun; Lukman Harun; Muhtarom Muhtarom (Universitas Islam Sultan Agung, 2026)
The main problem in this study is that many students consider mathematics a difficult subject to learn, which results in a lack of student motivation and passive, less participatory mathematics learning between teachers and students. This study aims to explore solutions to problems that arise in mathematics learning through the design thinking method, as outlined by David Kelley, which consists of 5 stages: empathize, define, ideate, Prototype, and test. In this problem exploration, 3 stages are used: empathize, define, and ideate to generate solution ideas from several possible solutions. The study population comprised 25 eighth-grade students and 3 mathematics teachers at SMP Al Islam, Mts Fathul Huda, and SMPN 2 Sayung. Data were collected using a Google Form questionnaire. The results of the data obtained are then analyzed from the empathize to the define stage. The results of this study indicate that the problem-based learning model, supported by GeoGebra and Canva, can improve students' problem-solving abilities. Based on the results of this exploration, researchers developed interactive media using the design thinking method to improve problem-solving abilities. Keywords: mathematics, interactive media, problem solving